The influence of after-school tutoring on the mental health of middle school students: A mediating effect test based on sleep deprivation and academic performance - Lianhua Fan; Ziqi Zhang; Xinyu Li (PLoS ONE, 2025)
Although Western studies have shown that adolescents’ mental health is intimately linked to after-school tutoring, very few studies have addressed this issue among Chinese adolescents. Herein, this study investigated the effect of after-school tutoring on students’ mental health using an empirical method and a mediation-effect test analysis. Based on 3581 China Education Panel Survey samples, results showed that sleep duration and academic performance act as mediators in the effect of after-school tutoring on students’ mental health. After-school tutoring leads to depressive emotions in students through sleep deprivation, playing a partial mediating effect (Z = 2.785, p < 0.05). Academic performance is another factor leading to students’ depressive emotions, similarly passing the mediation effect test (Z = 2.817, p < 0.05). Overall, after-school tutoring affects students’ mental health by depriving them of sleep time, hence influencing their academic performance. We suggest the following. First, the regulation of off-campus tutoring should be strengthened. Second, efforts should be made to alleviate parents’ educational anxiety. Lastly, students’ sleep quality should be ensured, and attention should be paid to monitoring their mental health status.